On the analytical solution of the Cauchy problem for a linear set-valued differential equation with a Hukuhara derivative - Komleva, Tatyana A.; Plotnikov, Andrej V.; Skripnik, Natalia V. (CUBO, A Mathematical Journal, 2026)
The article considers the Cauchy problem for a linear set-valued differential equation with the Hukuhara derivative and derives an analytical formula for its solution.